Twofold Pauson-Khand reaction of cyclic diynes in supercritical ethylene - Rausch, Bernhard J.; Becker, Heike; Gleiter, Rolf; Rominger, Frank (Synlett, 2002)
The cyclic diynes 1 and 7-11 were allowed to react in supercritical (sc) ethylene under Pauson-Khand conditions to give the tricyclic diketones 4 and 12-16 in yields between 47% and 15%, respectively. Our investigations reveal that in the case of cyclic diynes the yields of Pauson-Khand reactions in organic solvents can be tripled, by carrying out the syntheses in supercritical ethylene. The geometry of the resulting sulfur substituted diones 14 and 15 was determined by means of X-ray analysis on single crystals. Additionally, the synthesis of the twofold tethered cyclopentadienes 17 and 18 and the bis(tricarbonyl-manganese) complexes 19a and 19b from tricyclic dione 4 is presented.
Publikationsdatum: 07. Februar 2007 (online)
Gesehen am 11.11.2020